Digital Rights Management (Trinity Journal of Management, IT & Media (TJMITM), 2017)
A digital rights management (DRM) system designed for digital  document protection is presented in this paper. DRM  technologies include technologies that can be used to impose  direct functionality restrictions on digital content. Technologies  can be designed to effectuate the concept of self help such as  disabling access to the database or to some portion of the  database if the system detects an attempt to engage in some sort  of impermissible action, or detects unauthorized files residing on  the user's computer. Digital Rights Management (DRM) involves  the description, layering, analysis, valuation, trading and  monitoring of the rights over an individual or organization's  assets; both in physical and digital form; and of tangible and  intangible value. This paper will discuss some background information on the  protection of documents, the various technical measures  employed by this DRM system. The technical measures include  a variety of tamper-resistance methods, controlled execution  techniques, encryption, digital watermarking and other  techniques. Concept and limitations and future directions of the  technology are made throughout.
Keywords: Digital rights management; restrictions; digital content; digital watermarking; tamper-resistance method